Description of Entrepreneurial Characters of Mathematics Education Department Students of UPS Tegal in Calculus Class - Oktaviani, Dian Nataria; Lestiana, Herani Tri (Unnes Journal of Mathematics Education, 2017)
Developing entrepreneurial characters and skill is one of the goals of Faculty of Teacher Training and Education Pancasakti University Tegal. To achieve this goal, the learning process needs to support the development of entrepreneurial characters, such as self-confidence, hard work and unyielding, cooperative, independent, and active and creative. Learning activities should be able to provide opportunities for students to participate actively. Therefore, this study aimed at designing a Maple-integrated workbook to help students establish their entrepreneurial character. The workbook helps students build the character of independent in learning calculus, active and cooperative in solving problems, and creative in using Maple to explore the concept of calculus. This study employed Research and Development by adapting Borg and Gall's steps, which are preliminary information, design, preliminary development, validation and preliminary revision, field test and final revision. The entrepreneurial characters instrument is a questionnaire comprising statements that reflect the characters of entrepreneurship, which are self-confident, hard work, cooperative, independent, and active and creative. The result of questionnaire analysis showed that in general students’ entrepreneurial characters are in a good category, with the average score of entrepreneurial character is 2.85 out of 4.